Pengaruh Posisi Bukaan Tempat Penyimpanan Makanan Jadi Pedagang Kaki Lima Terhadap Angka Kuman - Afrida Nur Fauzia; Mohammad Mirza Fauzie; Choirul Amri (Poltekkes Kemenkes Yogyakarta, 2010)
Most street vendors heedless to the placement of their cart because of the limitation of the available area. This condition may influence the safety of their consumers due to the potential contamination which comes from air micro-organisms. To identify which of the stall opening positions that are safer, this experimental study were carried out. Result of laboratory examination showed that the average total plate count in position A (i.e. against with the street) was 252 colony/hour/100 cm2, position B (i.e. same direction with traffic) was 319 colony/hour/100 cm2, position C (i.e. opposite with traffic direction) was 392 colony/hour/100 cm2, and position D (i.e. facing the street) was 701 colony/ hour/100 cm2. The data analysis showed that the differences in air microbe number among those stall opening variations were significant. Since the posi-tion D was the highest number, it is suggested that the street vendors should pay attention to this opening position in order to prevent their commodity from contamination.